A dimensão do político na psicologia social no Brasil (1986-2011): uma análise da produção científica a partir da teoria democrática radical e plural - Frederico Alves Costa (2014)
The aim of this dissertation is to analyze the concept of political in a sample of the Brazilian social psychology production published in scientific journals from the 1986 to 2011. The crisis of social psychology, criticizing the dominant perspective in social psychology at the time, produced an important debate on the political character of knowledge production, linking it to the struggle against the social problems and the possibility of social change in Brazil. To that extent, it conceives that the crisis of social psychology, along with the awakening of the discussion about the concept of political in other fields of the human sciences, give relevance to questioning the way the concept of political has been discussed in the Brazilian social psychology production. Conceiving antagonism as the defining element of political, this dissertation focuses the debate in a perspective that understands political in the field of division, of distinction between friendenemy, considering hostility and violence as inherent to human sociability. In that perspective, this research also criticizes the comprehension of social relations politicization as a rational mediation, and we conceive the absence of any last foundation of reality as an relevant condition to the political in modern times, defining political unity as contingency that results from a hegemonic construction. Democracy is understood as something to come, been impossible to reach a reconciled society or even the junction between ethics and politics. From the goal of this dissertation and this conception of political our analysis focuses on the different forms of social relations politicization (the emerging of a political subject) and its consequences to democracy (societys utopia), having as a theoretical reference the Plural and Radical Democratic Theory developed by Ernesto Laclau and Chantal Mouffe. Social psychology production was categorized into the following analytical strands: last foundation of reality, rational subject, ethical-political subject, antagonism. By the end of this dissertation we present a research and intervention proposal in social psychology, as to contribute to the continuing crisis of the field, keeping present a critical review of what has been produced and building a social psychology that does not deny the political.